1983
DOI: 10.1128/iai.40.2.766-772.1983
|View full text |Cite
|
Sign up to set email alerts
|

Experimental infection of the New World owl monkey (Aotus trivirgatus) with hepatitis A virus

Abstract: Epidemiological studies have demonstrated the susceptibility of the owl monkey (Aotus trivirgatus) to hepatitis A virus, but have not shown an association between infection and histopathological or chemical evidence of liver disease. Therefore, 12 seronegative, colony-bred monkeys were inoculated intravenously with a fecal suspension containing either PA33 strain hepatitis A virus (a strain recovered from a naturally infected Aotus sp.) or HM-175 virus (recovered from a human). Viral antigen was detected by ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…Animal studies have shown that stool filtrates of patients or animals infected with HAV inoculated orally or intravenously, were infectious (Dienstag et al 1975;LeDuc et al 1983;Purcell et al 2002). Surprisingly, for a virus that is normally transmitted by the fecal-oral route, the wild-type HAV was shown to be 3.1 9 10 4 -fold less infectious by the oral, compared with the intravenous, route in tamarins and chimpanzees.…”
Section: Hepatitis a Virusmentioning
confidence: 99%
“…Animal studies have shown that stool filtrates of patients or animals infected with HAV inoculated orally or intravenously, were infectious (Dienstag et al 1975;LeDuc et al 1983;Purcell et al 2002). Surprisingly, for a virus that is normally transmitted by the fecal-oral route, the wild-type HAV was shown to be 3.1 9 10 4 -fold less infectious by the oral, compared with the intravenous, route in tamarins and chimpanzees.…”
Section: Hepatitis a Virusmentioning
confidence: 99%
“…Chimpanzees, as well as several species of New World monkeys, including marmosets, tamarins, owl monkeys, and Saimiri monkeys, are susceptible to HAV and may be infected by either oral or percutaneous challenge 27–30. Much has been learned from these nonhuman primate models of hepatitis A, although they do not recapitulate the disease perfectly.…”
Section: Disease Pathogenesismentioning
confidence: 99%
“…HAV was detected in saliva and the tonsil of one inoculated chimpanzee [Cohen et al, 19891, suggesting that the virus might have replicated in the oropharynx. Recently, HAV antigen was detected in epithelial cells of the duodenum in orally inoculated marmosets [Karayannis et al, 19861, but subsequent data did not confirm those findings [Karayannis et al, 19881. Owl monkeys are susceptible to infection with HAV by both intravenous and intragastric routes of inoculation [Lemon et al, 1982;LeDuc et al, 1983;Trahan et al, 19871. In this study we used owl monkeys to study pathogenesis of HAV infection following the natural oral route of inoculation in an attempt to detect extrahepatic sites of primary HAV replication and determine temporal relationships between appearance of infectious HAV and HAV antigens in stools, tissues, and body fluids, and the development of histopathological changes and immunological responses.…”
Section: Introductionmentioning
confidence: 99%